MANAGING CHANGE IN WARTIME: CHOOSING MODELS AND APPROACHES (Development Service Industry Management, 2025)
The article provides an in-depth analysis of various theoretical approaches to interpreting the essence of the concept of “change management” and its key tasks. The study highlights the evolution of change management as a distinct discipline and emphasizes its differences from general enterprise management, particularly in conditions of uncertainty and rapid environmental transformations. The author critically examines the fallacy of equating change management with traditional managerial practices, arguing that it requires a more dynamic and adaptive approach.A significant focus is placed on modern change management models, which prioritize leadership, strategic communication, and the active engagement of employees in the transformation process. The article explores how these models facilitate smoother transitions within organizations and enhance their resilience in times of crisis. Through a comparative analysis of widely recognized contemporary change management frameworks, the research identifies their strengths and limitations while offering recommendations for their practical adaptation in real-world business environments.Moreover, the study pays particular attention to the challenges posed by wartime conditions, where enterprises must navigate extreme uncertainty, resource constraints, and heightened risks. The article substantiates the key components necessary for selecting effective methods and approaches to influencing personnel in such conditions. Special emphasis is placed on fostering organizational agility, ensuring psychological support for employees, and maintaining operational stability amid ongoing disruptions.Ultimately, the article provides valuable insights into how organizations can develop robust change management strategies that not only address current challenges but also build a foundation for long-term resilience and sustainable growth.
Keywords: change management; management; leadership; management models; stages of change implementation; impact on staff